2017
DOI: 10.3847/1538-4357/aa9932
|View full text |Cite
|
Sign up to set email alerts
|

The Lyα Reference Sample. VIII. Characterizing Lyα Scattering in Nearby Galaxies

Abstract: We examine the dust geometry and Lyα scattering in the galaxies of the Lyman Alpha Reference Sample (LARS), a set of 14 nearby ( < < z 0.02 0.2) Lyα-emitting and starbursting systems with Hubble Space Telescope Lyα, Hα, and Hβ imaging. We find that the global dust properties determined by line ratios are consistent with other studies, with some of the LARS galaxies exhibiting clumpy dust media, while others of them show significantly lower Lyα emission compared to their Balmer decrement. With the LARS imaging,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Lyα photons are not attenuated by dust if dust is confined in HI clumps (the clumpy ISMs ;Neufeld 1991;Hansen & Peng Oh 2006) because Lyα photons are scattered on the surface of clumps before being absorbed by dust. Scarlata et al (2009) find that the clumpy dust screen (ISMs) can reproduce observed line ratios of Lyα to Hα (or fesc(Lyα)), and Hα to Hβ (orE(B − V )) of local LAEs (see also Bridge et al 2017). It is, however, not clear what causes such a clumpy ISM geometry especially for LAEs.…”
Section: (Ii) Less Efficient Resonant Scattering In a Clumpy Ismmentioning
confidence: 99%
“…Lyα photons are not attenuated by dust if dust is confined in HI clumps (the clumpy ISMs ;Neufeld 1991;Hansen & Peng Oh 2006) because Lyα photons are scattered on the surface of clumps before being absorbed by dust. Scarlata et al (2009) find that the clumpy dust screen (ISMs) can reproduce observed line ratios of Lyα to Hα (or fesc(Lyα)), and Hα to Hβ (orE(B − V )) of local LAEs (see also Bridge et al 2017). It is, however, not clear what causes such a clumpy ISM geometry especially for LAEs.…”
Section: (Ii) Less Efficient Resonant Scattering In a Clumpy Ismmentioning
confidence: 99%
“…The difficulty in interpreting line-of-sight velocities and linewidths from Lyα emission is that resonant scattering diffuses the intrinsic Lyα radiation field in real and in the frequency space (see review by Dijkstra 2019). The spatial diffusion can be envisioned as a projected smoothing processes (Bridge et al 2018) that can enhance the apparent size of the Lyα blobs by reducing the steepness of their surface brightness profiles (Zheng et al 2011;Gronke & Bird 2017). Moreover, it can also "wash-out" cold-accretion features of small angular size (Smith et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although these are plausible explanations, physical reality is likely to be complicated by the detailed internal geometry of the central galaxy. Studies of the Lyα emission from starbursting systems have highlighted the complex role of dust content and geometry on the escaping radiation (Hayes et al 2013(Hayes et al , 2014Bridge et al 2017). At intermediate r p , 50 kpc, the emission flux is becoming more similar in the two subsamples and therefore less dependent on the SFR of the central galaxy.…”
Section: Dependence On Sfrmentioning
confidence: 99%